2017
DOI: 10.1108/jsbed-09-2016-0138
|View full text |Cite
|
Sign up to set email alerts
|

Firm capabilities, business model design and performance of SMEs

Abstract: Purpose The purpose of this paper is to investigate the relationships between firm capabilities, business model (BM) design, and firm performance. Design/methodology/approach The study provides a quantitative assessment of the proposed model using a sample of 411 small- and medium-sized enterprises. Heckman’s sample selection model is employed as an econometric framework. Findings The outcomes demonstrate that the adoption of a given BM is endogenous with respect to firm capabilities, different capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 112 publications
1
64
0
Order By: Relevance
“…The performance of the enterprise is one of the most important indicators for the evaluation of business results [82]. The relationship between BMI and business performance has been confirmed by several previous studies [29,55,83,84].…”
Section: Outcomes Of Bmimentioning
confidence: 54%
“…The performance of the enterprise is one of the most important indicators for the evaluation of business results [82]. The relationship between BMI and business performance has been confirmed by several previous studies [29,55,83,84].…”
Section: Outcomes Of Bmimentioning
confidence: 54%
“…Several authors point to the idea that when firms become larger, they are less vulnerable to the macro-economic situation [8], which is in contrast to the extended idea that SMEs adapt better to changes in the market because they present higher levels of strategic and operational flexibility due to their reduced size [11,26]. The adaptability of SMEs to changes in market conditions due to environment forces is based on flexibility and on the existence of a proactive attitude of the firm.…”
Section: Literature Reviewmentioning
confidence: 63%
“…However, there is a key difference between them. Class 1 represents all those SMEs that need to adjust their size to increase their flexibility [11,26]. In Spain, from 2011 to early 2015, 17,283 SMEs in the industrial sector had disappeared, all of which were manufacturers, which represents more than 12% of the total number of SMEs [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey by the International Council for Small Business (ICSB) revealed that SMEs constitute over 90 per cent of all businesses, create 60 per cent of all jobs and contribute to about 50 per cent of the Gross Domestic Product (GDP) of any country (Pucci et al, 2017). SMEs are described as businesses with between one and five hundred workers (Foroudi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%